Selective Nuclear Factor Kappa b (NFkB) Inhibitor, Pyrrolidium Dithiocarbamate Prevents, Long-Term Histologic Damage in Ischemia-Reperfusion Injuries after Delayed Testicular Torsion - Ozcan, Levent; Otunctemur, Alper; Polat, Emre Can; Ozbek, Emin; Kirecci, Sinan Levent; Somay, Adnan (Urology Journal, 2016)
Purpose: Nuclear factor kapa b (NFKB) is a transcription factor that is required for cytokine-mediated induction of the human inducible nitric oxide synthase (iNOS) gene. Recent studies have shown that in the pathophysiology of ischemia-reperfusion (IR) injuries NFKB is involved. In our study we aimed to determine the efficacy of the selective NFKB inhibitor, pyrrolidium dithiocarbamate (PDTC), on long-term histological damage in testicular IR injuries. Materials and Methods: Twenty-one adult male Wistar albino rats were divided into 3 equal groups. In groups 1-2, the left testes in rats underwent 4 hours of 720° experimental torsion. In group 2, PDTC (100 mg/kg) was administered intraperitoneally in the last 1 hour before detorsion; and group 3 underwent a sham operation. All rats underwent bilateral orchiectomy 45 days after the experiment. The testes weights were measured and compared to the other groups and their contralateral values. Testes samples were fixed with Bouin solution for histological (Johnsen score) and immunohistochemical examination. Immunohistochemically iNOS and an active subunit of NFKB, p65 were evaluated using mouse primary monoclonal antibodies and were evaluated semi quantitatively. Results: Testicular weights and Johnsen scores in ipsilateral testes were 0.67 ± 0.85, 1.54 ± 0.11, 1.84 ± 0.64 and 1.63 (1-4), 6.94 (4-10), 5.29 (1-9) in the torsion, sham and PDTC groups, respectively. In contralateral testes the same values were 1.74 ± 0.84, 1.59 ± 0.13, 1.50 ± 0.54 and 5.38 (2-8), 7.17 (5-10), 6.30 (4-9). Testicular weights and Johnsen scores were significantly different in the ipsilateral torsion group (P < .05). In the PDTC group testicular weights and Johnsen scores were similar with the control group (P > .05). Immunohistochemically there was marked staining in the iNOS and p65 expressions in the torsion group compared with group 2 and 3. In rats administered PDTC, iNOS and p65 expressions were significantly reduced compared with the torsion group. There were no significant differences between the histological and immunohistochemical results of groups 2 and 3. Conclusion: This data suggests that IR induces iNOS expressions through the activation of NFKB, p65. The NFKB pathway plays major role in testicular reperfusion injuries. It is possible to prevent reperfusion injuries using selective the NFKB inhibitor.